Chamilo platform and the learning management system in the students of the technical careers of Cenfotec of the UNHEVAL - Huánuco 2015 - Ascayo-León, Orlando (2023)
The study was carried out with the aim of improving the management of learning in the students the application of the chamilo platform, for which a quasi-experimental design of pre- and post-test was applied to a population of 300 students of the technical careers of cenfotec of the unheval from which a sample of 18 students was extracted to which the instruments designed based on the learning management system were applied over a period of 5 months. The evaluation of the results when measuring the learning management system, and as an effect of the application of the chamilo platform. We have the evaluation of the results when measuring the learning management system, and as an effect of the application of the chamilo platform in the learning sessions and the development of the management system, we have a greater predominance of the interaction and communication tool (44.4%) in the pre-test and in the post-test the inter action and communication tool predominates (83.3%). Within the above conclusions we can affirm that the students that the research carried out, being the development of the application of the learning management system in the students of the technical courses of CENFOTEC of the UNHEVAL, is part of the conclusions reached by the students. Cited research, and it was obtained as a result in the research, that executing the activities programs has improved learning management system in the students and specifically in the Interaction and communication tool.